Lysias’ Chronology and the Dramatic Date of Plato’s Republic - Verlinsky, Alexander (Hyperboreus, 2015)
In the ﬁrst part of the paper the author argues that Lysias’ biographic dates as according to ancient tradition (Dion. Hal. Orat. vet. Lys. p. 8. 5 ff. Us.–R.; Ps.-Plut. Vit. X or. 835 c) – birth in 459/8 BC and the departure for Thurii in 444/3 – which are regarded as untrustworthy by the vast majority of scholars – are indeed reliable. The author argues that the note of Ps.-Plut. that Lysias’ father Cephalus died before this departure, which provoked various revisions of Lysias’ chronology, is itself a mistake. Сephalus’ arrival in Athens cannot be dated much earlier than 460 BC, because he was invited to Athens by Pericles, nor much later than this date, because Lysias had already been born in Athens; since Cephalus lived in Athens for thirty years (Lys. 12. 4), he accordingly died around 430 BC. In the second part of the paper the author readdresses the related subject of the dramatic date of Plato’s Republic. The participation of Cephalus at a very advanced age in the introductory talk thus implies a dramatic date sometime around 430 BC, as according to the proposal of K. F. Hermann, nowadays entirely forgotten after its refutation by A. Boeckh who pleaded for a date of 411/10 BC. An additional argument for the ca. 430 date is provided by the initial celebration of the festival in honor of the Thracian goddess Bendis, during which the conversation takes place. The most plausible date for the inauguration of this festival is ca. 430 BC for the following reasons: Bendis became the state divinity no later than 429 BC; the decree that regulates the worship of Bendis (IG I3 136) and mentions the pannychis and the procession, which also feature in the Republic, should be certainly dated after 431 BC, the outbreak of the Peloponnesian War; contrary to attempts to date the decree 413 BC – based in part on the alleged later dramatic date of the Republic and in part on the assumption that the decree concerns the expanded form of the festival and not its initial introduction there are considerable reasons in favor of the date ca. 430 BC: Socrates’ words in the Republic unambiguously show (1) that he was present at inauguration of the festival and (2) that the procession and the pannychis were already in place; accordingly there is no reason to suppose any later accretions to the festival, as C. Planeaux rightly argued. It is further implausible that the celebration was inaugurated much later than Bendis becoming the state divinity, i.e. than 429 BC; moreover, friendly relations with Thrace were important for Athens in the late 430s and early 420s – but not in the 410s. Contrary to the opinion of A. Boeckh and many scholars after him, the various ages of the dramatis personae of the Republic do not contradict the circa 430 date, provided one admits that Plato’s brothers Adeimantus and Glaucon were some twenty years older than he (i.e. were born about 450 BC).